Ekocid - det bortglömda brottet. Om lämpligheten att införa ekocid som ett femte internationellt brott i Romstadgan - Stenkvist,Alva (2020)
This essay examines the possibility to make environmental destruction an international crime by including ecocide as a fifth crime against peace in the Rome Statute of the International Criminal Court adopted in Rome in 1998. The issue is examinated in relation to the purpose and objective of the Statue and in relations to the core crimes. The core crimes; crime of genocide, crimes against humanity, war crimes and crime of aggression are to be seen as the most serious crimes of concern to the international community as a whole. In the first part of the essay an account is given of the background of ecocide and the Rome Statue. The background and definition of the core crimes is also given. When it comes to ecocide the crime was for a long time a part of the draft of the Statue. However, when the Statue was about to be signed ecocide was eliminated from the draft. Today the debate has resumed regarding the establishment of ecocide as an international crime in the Rome Statue. Some even argue that the crime never should have been eliminated and that ecocide is a missing core crime. In the latter part of the essay an investigation of the main issue is made. It is examinated how well ecocide would serve as a crime in the Rome Statue and if ecocide and the core crimes share the same common of interests. Furthermore, the paper examine if the crime of ecocide share the same purpose och objective as the Rome Statue. It is also discussed whether ecocide can be concidered as a crime that goes under the jurisdiction of the ICC.
Keywords: folkrätt; public international law; ekocide; ecocide; internationell miljörätt; internationell straffrätt; storskalig miljöförstöring; Romstadgan; Romstadgan för internationella brottmålsdomstolen; ICC; International Criminal Court